Integrative Genomic Insights into Coral Resilience: Adaptive and Acclimatory Responses to Seasonal Environmental Shifts - Ghanim, Tasnim (AUC Knowledge Fountain, 2024)
Coral reefs, critical to marine biodiversity and coastal protection, face escalating threats from climate change-related phenomena such as ocean warming. This warming is leading to widespread thermal stress that contributes to coral bleaching and infectious disease in corals, leading to the disruption of marine ecosystems and the economies that depend on them. Focusing on the brain coral Platygyra daedalea, known for its thermal resilience in the Persian Arabian Gulf—a region that exemplifies the extreme stressors of climate change—our study aims to dissect the genetic, transcriptomic, and microbiological underpinnings of coral survival in high-temperature environments predicted for the end of the century. We examined population-specific genetic resilience, finding variations in adaptability across different coral cohorts. The study uncovered distinct gene expression profiles and essential genetic diversity patterns linked to the coral's ability to withstand environmental stress, shedding light on the genetic and bacterial microbiome-driven adaptive mechanisms of P. daedalea. These findings highlight the significance of genetic variations and symbiotic microbial interactions in coral resilience, providing crucial insights into adaptation and acclimation strategies.